A Method of Catalytic Neutralization of Exhaust Gases with Nitrogen Oxides (Eurasian Research Bulletin, 2022)
In this article, the effectiveness of the nitrogen oxide exhaust gas purification process, the problems and solutions of the temperature dependence of the reaction are explained in detail. In this process, nitrogen oxides are reduced to nitrogen in the presence of reducing gas on the catalyst surface at high temperatures. In this case, the temperature of the catalytic process also depends on the type of gas regenerator used in the recovery process.